Is Faith in God Decadent? - Ladd, George Trumbull (Harvard theological review, 1912)
Much the most important change in theological opinion which has taken place during the last half-century has reference to an altered conception of God, and, as an inevitable consequence, of his relations to the world of things and of men. This change was originally neither initiated nor approved by theologians themselves. It was rather commended to them, or even forced upon them, by modern science and modern philosophy. The attitude, however, of these two sources, or prime causes, of change toward the questions involved and toward the then reigning theological position on these questions was in certain important respects markedly different. Physical and natural science, proceeding painstakingly but rapidly by means of experimental methods, and making use of the facts discovered by these methods as a basis for induction, arrived at a quite new conception of Nature.